Traditional games resulted in post-exercise hypotension and a lower cardiovascular response to the cold pressor test in healthy children - Rauber, Suliane B.; Boullosa, Daniel A.; Carvalho, Ferdinando O.; de Moraes, José F. V. N.; de Sousa, Ioranny R. C.; Simões, Herbert G.; Campbell, Carmen S. G. (Frontiers in Physiology, 2014)
The present study aimed to verify if blood pressure (BP) reactivity could be reduced through a previous single session of active playing when compared to sedentary leisure. Sixteen pre-pubertal healthy children participated in this study. After familiarization with procedures and anthropometric evaluation, participants performed three sessions in randomized order: (1) 30 min of traditional Brazilian games (PLAY); (2) 30 min of video game playing (DDR); and (3) 30 min of watching TV (TV). Each session lasted 80 min, being 10 min of rest; 30 min of intervention activity; and 40 min of recovery. After recovery, the Cold Pressor Test (CPT) was used for the assessment of acute cardiovascular reactivity. BP was recorded at 30 s and 1 min during the CPT. Analysis of variance showed post-exercise hypotension (PEH) only after PLAY, and that systolic and diastolic BP were significantly increased in all conditions during CPT. However, the magnitude of the CPT-induced BP response was significantly less in PLAY compared to DDR and TV. The PEH observed during recovery and the reduced BP response to CPT following playing traditional games may be due its higher cardiovascular and metabolic demand as was indicated by the increased heart rate, oxygen consumption, and BP. It was concluded that BP reactivity to stress may be reduced through a previous single session of traditional games and that PEH was recorded only after this exercise form. This benefit indicates a potential role of playing strategies for cardiovascular health in childhood.